Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Pembelajaran terhadap Hasil Belajar Matematika - Nusi, Ireine G.C.; Nasir, Rahma; Hasbi, Muh.; Rizal, Muh. (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to analyze the effect of the Problem-Based Learning (PBL) model assisted by instructional media on the mathematics learning outcomes of Grade XI students at SMK Negeri 1 Palu in the 2024/2025 academic year. The research employed a quantitative approach using a quasi-experimental method with a Nonequivalent (Posttest Only) Control Group Design. The results showed that the average posttest score of the experimental group was 79.31, which was higher than the control group’s average posttest score of 66.93. It can be concluded that the implementation of the Problem-Based Learning (PBL) model assisted by instructional media had a positive effect on the mathematics learning outcomes of Grade XI students at SMK Negeri 1 Palu in the 2024/2025 academic year.   Keywords: Learning Outcomes; Mathematics Education; Problem Based Learning; Learning Media